5(x+2)=3(29-2x)

Simple and best practice solution for 5(x+2)=3(29-2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+2)=3(29-2x) equation:


Simplifying
5(x + 2) = 3(29 + -2x)

Reorder the terms:
5(2 + x) = 3(29 + -2x)
(2 * 5 + x * 5) = 3(29 + -2x)
(10 + 5x) = 3(29 + -2x)
10 + 5x = (29 * 3 + -2x * 3)
10 + 5x = (87 + -6x)

Solving
10 + 5x = 87 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
10 + 5x + 6x = 87 + -6x + 6x

Combine like terms: 5x + 6x = 11x
10 + 11x = 87 + -6x + 6x

Combine like terms: -6x + 6x = 0
10 + 11x = 87 + 0
10 + 11x = 87

Add '-10' to each side of the equation.
10 + -10 + 11x = 87 + -10

Combine like terms: 10 + -10 = 0
0 + 11x = 87 + -10
11x = 87 + -10

Combine like terms: 87 + -10 = 77
11x = 77

Divide each side by '11'.
x = 7

Simplifying
x = 7

See similar equations:

| 4m^2-41m+10=0 | | 2p-12=11-2p | | -[7x+[-4x+(-2+4x)]-(5x+1)]=0 | | -5n+9+7n=7n-8n-9 | | 8+13x=216 | | 1/5 | | 4x-17=2x+4 | | f(x)=8cosx | | -4y-9=6y+11 | | -2x^2-x=20 | | 11/2X=10 | | X^2+2x+4=3 | | 3(x+5)+2x=5x-15 | | 6x+7x+8=540 | | x^2-(m+1)*x+m=0 | | x^5-7x^3+9x=-x | | 6x+7x+8=360 | | x/187 | | (8,3)x= | | 3(10+x)=3 | | 6x+7x+8=36 | | x-41=-6 | | 12x-3-2x=0 | | 6/7a=16 | | 6x+3-9x=12-15x+12x-9 | | 4a^2+12a-27=0 | | (2/3)x=-9 | | 1/3d(60-t) | | -2(-7+3x)=-22 | | 3(2c-1)-2=2c+3 | | 6(10-3x)=10-8x | | m-20=10 |

Equations solver categories